An insight into the Professional Culture of Indian Engineering Students: to Face Challenges of Industry 4.0 - Prusty, Chitrita; Kumar Das, Ranjit; K.Dwivedy, A. (International Journal of Engineering and Technology, 2018)
To leverage the best that technology has to offer us, India must embrace Industry 4.0. Implementing Smart manufacturing will usher in a new phase of industrialisation in India. However one of the major problems that India will face is lack of skilled labour. To manage this short coming higher education department should make changes to the engineering education scenario. While making changes they should keep in mind their occupational culture. For this a thorough understanding of the professional culture is of primary importance. This article examines the occupational culture of the Indian engineering students by studying their communicative performances. Students have been interviewed. Bantzâ€™s Organizational Communication Culture (OCC) methodology has been used to analyze the messages to find traces of this culture. The findings derived from a study adopting such method can have important implications for practitioners as it will help them provide the Indian engineering students proper guidance and make them ready to meet the challenges of industry 4.0.The various characteristics of this culture that these students possess if harnessed properly by upgraded educational system can help India leverage the best of Industry 4.0. Â Â